Blood-Pressure and Cholesterol Lowering in Persons without Cardiovascular Disease - Yusuf, Salim; Lonn, Eva; Pais, Prem; Bosch, Jackie; López-Jaramillo, Patricio; Zhu, Jun; Xavier, Denis; Avezum, Alvaro; Leiter, Lawrence A; Piegas, Leopoldo S; Parkhomenko, Alexander; Keltai, Matyas; et al. (The New England journal of medicine, 2016)
BACKGROUND: Elevated blood pressure and elevated low-density lipoprotein (LDL) cholesterol increase the risk of cardiovascular disease. Lowering both should reduce the risk of cardiovascular events substantially. METHODS: In a trial with 2-by-2 factorial design, we randomly assigned 12,705 participants at intermediate risk who did not have cardiovascular disease to rosuvastatin (10 mg per day) or placebo and to candesartan (16 mg per day) plus hydrochlorothiazide (12.5 mg per day) or placebo. In the analyses reported here, we compared the 3180 participants assigned to combined therapy (with rosuvastatin and the two antihypertensive agents) with the 3168 participants assigned to dual placebo. The first coprimary outcome was the composite of death from cardiovascular causes, nonfatal myocardial infarction, or nonfatal stroke, and the second coprimary outcome additionally included heart failure, cardiac arrest, or revascularization. The median follow-up was 5.6 years. RESULTS: The decrease in the LDL cholesterol level was 33.7 mg per deciliter (0.87 mmol per liter) greater in the combined-therapy group than in the dual-placebo group, and the decrease in systolic blood pressure was 6.2 mm Hg greater with combined therapy than with dual placebo. The first coprimary outcome occurred in 113 participants (3.6%) in the combined-therapy group and in 157 (5.0%) in the dual-placebo group (hazard ratio, 0.71; 95% confidence interval [CI], 0.56 to 0.90; P=0.005). The second coprimary outcome occurred in 136 participants (4.3%) and 187 participants (5.9%), respectively (hazard ratio, 0.72; 95% CI, 0.57 to 0.89; P=0.003). Muscle weakness and dizziness were more common in the combined-therapy group than in the dual-placebo group, but the overall rate of discontinuation of the trial regimen was similar in the two groups. CONCLUSIONS: The combination of rosuvastatin (10 mg per day), candesartan (16 mg per day), and hydrochlorothiazide (12.5 mg per day) was associated with a significantly lower rate of cardiovascular events than dual placebo among persons at intermediate risk who did not have cardiovascular disease. (Funded by the Canadian Institutes of Health Research and AstraZeneca; ClinicalTrials.gov number, NCT00468923.).
Keywords: senioři; Cholesterol, LDL; dvojitá slepá metoda; Medication Adherence; Double-Blind Method; rosuvastatin kalcium; Hypertension; Hydrochlorothiazide; Biphenyl Compounds; Drug Therapy, Combination; Middle Aged; mužské pohlaví; benzimidazoly; Benzimidazoles; Rosuvastatin Calcium; tetrazoly; bifenylové sloučeniny; Hydroxymethylglutaryl-CoA Reductase Inhibitors; antihypertenziva; Cardiovascular Diseases; Antihypertensive Agents; kombinovaná farmakoterapie; ženské pohlaví; hydrochlorthiazid; Humans; statiny; adherence k farmakoterapii; hypertenze; lidé středního věku; rizikové faktory; Tetrazoles; LDL-cholesterol; Female; Aged; Risk Factors; kardiovaskulární nemoci; lidé; Male